KARAKTERISTIK PETANI DAN KELAYAKAN USAHATANI JAHE DI SUMATERA UTARA (Farmer Characteristics and Farming Feasibility of Gingers in North Sumatera) - RITA HERAWATY BANGUN (Universitas Mulawarman (University of Mulawarman), 2021)
The success of agricultural efforts depends on the competency of farmers as primary organizers. Characteristics related to competencies such as farmer education level, farmer age, financing, and institutional participation. The purposes of this research were to identify the characteristics of ginger farmer and to analyze the feasibility of ginger farming in North Sumatera. This research used secondary data. Descriptive analysis was a method of analysis used in research. The results of identifying show that characteristics of ginger farmers in North Sumatera were as much as 61.76% being at the age of 25 to 54 years, 55.24% of ginger farmers completed education until junior level, 96.79% of ginger farmers financed their own farming activities, 95.06% of farmers sold their products to the collector merchants, and the involvement of farmers in agricultural institutions were very small. Revenue Cost Ratio (R/C Ratio) of ginger in North Sumatera is 1.97, meaning that each expenditure of IDR1,00 then the ginger farmer will get a receipt of IDR1.97. This shows that ginger farming is viable and beneficial to be cultivated. Maximizing agricultural extension role as one of the efforts to increase the income and welfare of ginger farmers in North Sumatera.